A generalized kinetic model for electro-assisted catalytic wet air oxidation of triclosan on Ni@NiO/graphite electrode. (31st August 2020) - Sun, Min; Hong, Xiao-Hui; Tao, Xiong-Fei; Zhai, Lin-Feng; Wang, Shaobin
Highlights: Electro-assisted catalytic wet air oxidation kinetics of triclosan (TCS) is studied. Mineralization of TCS follows a pseudo-first order kinetics. A kinetic model to describe mineralization of TCS at varied operation conditions. Effects of operating parameters on TCS mineralization rates are discussed. Optimized operation condition is suggested for ECWAO process in treating PPCPs. Abstract: Electro-assisted catalytic wet air oxidation (ECWAO) is an efficient technique for wastewater treatment under ambient condition. In this work, the mineralization kinetics of triclosan (TCS) in an ECWAO process with Ni@NiO/graphite-felt (GF) electrode is studied. The TCS mineralization follows a pseudo-first order kinetics in the ECWAO process. A general kinetic model, based on the depletion of total organic carbon (TOC) as a lumped parameter, is developed. Such a kinetic model suggests the optimized ECWAO operating conditions of initial concentration of TOC at 40 mg L −1, applied current at 25 mA, and temperature at 308 K. In addition, the ECWAO is also effective for the treatment of biosphenol A (BPA) and sulfamethoxazole (SMX). Under the optimal conditions, TCS, BPA and SMX are mineralized by 92.9 ± 1.5, 90.8 ± 1.7 and 90.6 ± 1.0% within 120 min, with specific energy consumptions ( SECs ) of 2.2 ± 0.3, 1.4 ± 0.5, and 2.8 ± 0.6 kW h kg-TOC −1, respectively.